An oxygen-coordinated molybdenum single atom catalyst for efficient electrosynthesis of ammonia. Issue 44 (4th May 2021) - Geng, Jing; Zhang, Shengbo; Xu, Hui; Wang, Guozhong; Zhang, Haimin
Abstract : The Mo–O coordinated single-atom catalyst was successfully synthesized by utilizing surface oxygen-rich activated carbon as the adsorption regulator, as the electrocatalyst exhibits superior nitrogen reduction activity with high ammonia yield. Abstract : Electrochemical nitrogen (N2 ) reduction has been regarded as a promising strategy for artificial ammonia (NH3 ) production under ambient conditions. Herein, we report the fabrication of molybdenum (Mo) single atoms anchored on activated carbon (Mo-SAs/AC) for the electrochemical N2 reduction to NH3 . The surface-rich oxygen functional groups of activated carbon can effectively capture the Mo precursor, and concurrently act as the coordination sites to anchor Mo single atoms by forming Mo–O x bonds. As a result, the Mo-SAs/AC as an electrocatalyst shows high activity toward the N2 reduction reaction (NRR), affording an NH3 yield rate of 2.55 ± 0.31 mg h −1 mgMo −1 and a faradaic efficiency (FE) of 57.54 ± 6.98% at −0.40 V ( vs. RHE) in 0.1 M Na2 SO4 electrolyte with good stability and durability. The constructed Mo–O x sites are responsible for high NRR activity of Mo-SAs/AC.